Optimizing the contact center services of a Portugueses Electronics ands Appliances Retailer Company - Bandola, Susana Farinha (2013)
Nowadays the world is based on global economy with almost unlimited access to information where the technology development is a constant. This context led to a transformation on customers’ behavior that became more informed and demanding which obliges companies to have the adequate means to ensure time to market, create value and warranty a high level of quality service. Therefore the mass-marketing era seems to have already passed and be replaced by a one-to-one marketing approach. Thus, Customer Relationship Management is now one of the most important research fields to be studied in a Marketing context and applied in companies that want to be successful in a competitive business environment. Considering this new strategy that puts customers in the center of a company’s priorities, Contact Centers emerge as an extremely important tool to interact with customers through multiple channels. The concept of service provided in a Contact Center is now seen in a wide perspective, involving all the phases of contact between customers and the organization. Furthermore, the products and services offered by Contact Centers are becoming more sophisticated which implies a more elaborated strategy of customers’ relationship and gives companies new challenges to face. Taking into account all the aspects mentioned above, this project aims to suggest new ways of optimizing the Contact Center services of a Portuguese company, specialized in the electronics and appliances retailer business, with the final aim of maximize customers’ satisfaction, improve their loyalty and exceed their expectations.